Iḷaṅkōviṉ ilakkiya uttika - Cuppiramaṇiyan̲, Ca. Vē. (Ulakat Tamiḻārāycci Niṟuvaṉam, 1984)
Study of the literary techniques of Iḷaṅkōvaṭikaḷ, Tamil poet and author of Cilappatikāram, Tamil epic.
In Tamil.
Includes bibliographical references (p. [202]-203).
Study of the literary techniques of Iḷaṅkōvaṭikaḷ, Tamil poet and author of Cilappatikāram, Tamil epic.